Optimization of a single phase rectangular microchannel heat sink cooling system - Zaidan, Husain (2015)
A simple thermal resistance network model is developed to optimize the overall thermal performance of a single layer rectangular water-cooled micro-channel heat sink made from silicon which has a very high thermal conductivity. The object of this optimization is the minimization of the overall thermal resistance, firstly in series and secondly in series and parallel. The thermal resistance consists of the conduction resistance, convection resistance and bulk resistance due to the bulk temperature rise of the coolant. The conduction resistance is normally a small part of the overall resistance. The heat sink under consideration has a width and length of W ? L =1cm×1cm. The thickness of the base of the micro-channel is ???????? =100[????],and the depth of the micro channel ????=365[????] ,In the current study, minimization of the overall thermal resistance of a micro-channel heat sink is carried out using genetic algorithm,(GA). The fin thickness ww and the channel width wc are the optimized variables under a fixed coolant volume flow rate. Results obtained agreed well with previous experimental studies.